(untitled) (Bangladesh Journal of Dental Research & Education, 2015)
Dental students represent the educated, urbanized, influential and motivated class of individuals. If motivated for oral health, they can transfer the same knowledge and behavior patterns to patients during their practices. With this intention, this study was planned. 200 dental students were assessed by a close-ended, four-item questionnaire. Oral hygiene was assessed by Simplified Oral Hygiene Index (OHI, Greene and Vermilion, 1964) and gingival condition by Gingival Index (GI, Loe & Silness, 1963). A positive change in attitude was observed from first to final year students. 100% of them used tooth brush and paste, but 88%, 88% 96%, 92% in first, second, third and fourth year cleaned their tongue; whereas 70%, 92%, 94%, 92% of them, respectively, were in favor of scientific method of brushing. 92%, 90%, 96%, 100%, respectively, felt visiting the dentist during gingival bleeding. Also, there was statistically significant improvement in GI between first and final year (p=0.00005), between second and final year (p=0.0003) students. OHI showed a consistent improvement from first to final year (p<0.05). A positive change in attitude with reduction in GI and OHI status was observed with the increase in professional years. Key message: The attitude towards periodontal care is quite unsubstantial and oral hygiene status, gingival condition among first and second year dental students is poor as compared to third year and final year students. So, there is need to bring about a change in the attitude and improvement in oral hygiene status and gingival condition of dental students from their initial years of learning. Bangladesh Journal of Dental Research and Education Vol.5(2) 2015: 44-48